A drug carrier targeting murine uPAR for photodynamic therapy and tumor imaging. (1st September 2015) - Zhou, Xiaolei; Zheng, Ke; Li, Rui; Chen, Zhuo; Yuan, Cai; Hu, Ping; Chen, Jincan; Xue, Jinping; Huang, Mingdong
Graphical abstract: Abstract: Photodynamic therapy (PDT) has been used as an effective therapeutical modality for tumors. In PDT, a photosensitizer was used to capture the light of specific wavelength, leading to the generation of reactive oxygen species and cytotoxicity surrounding the photosensitizer. Modifications of photosensitizers to enhance tumor specificity are common approaches to increase the efficacy and reduce the side effects of PDT. Previously, we developed a human serum albumin (HSA)-based drug carrier fused with the human amino-terminal fragment (hATF), which binds to a tumor surface marker (urokinase receptor, uPAR). However, hATF-HSA binds to murine uPAR much weaker (79-fold) than to human uPAR, and is not optimal for applications on murine tumor models. In this study, we developed a murine version of the drug carrier (mATF-HSA). A photosensitizer (mono-substituted β-carboxy phthalocyanine zinc, CPZ) was loaded into this carrier, giving a rather stable macromolecule (mATF-HSA:CPZ) that was shown to bind to murine uPAR in vitro . In addition, we evaluated both the photodynamic therapy efficacy and tumor retention capability of the macromolecule (at a dose of 0.05 mg CPZ/kg mouse body weight) on murine hepatoma-22 (H22) tumor bearing mouse model. mATF-HSA:CPZ showed more accumulation in tumors compared to its human counterpart (hATF-HSA:CPZ) measured by quantitative fluorescence molecular tomography (FMT). Besides, mATF-HSA:CPZ exhibited a higher tumor killing efficacy than hATF-HSA:CPZ. Together, the macromolecule mATF-HSA is a promising tumor-specific drug carrier on murine tumor models and is an useful tool to study tumor biology on murine tumor models.